Assessing food security using household consumption expenditure surveys (HCES): a scoping literature review. Issue 12 (16th April 2018) - Russell, Joanna; Lechner, Anne; Hanich, Quentin; Delisle, Aurélie; Campbell, Brooke; Charlton, Karen
Abstract: Objective: To meet some of the UN's seventeen Sustainable Development Goals by 2030, there is a need for more effective policy to reduce food insecurity in low-income and lower-middle-income countries (LMIC). Measuring progress towards these goals requires reliable indicators of food security in these countries. Routinely conducted household consumption and expenditure surveys (HCES) provide potentially valuable and nationally representative data sets for this purpose. The present study aimed to assess methods used to determine national food security status using proxy measures from HCES data in LMIC globally. Design: A scoping literature review was conducted using electronic databases. Of the 929 abstracts identified, a total of twenty articles were reviewed against strict inclusion and exclusion criteria and included for further analysis. Results: Fourteen LMIC globally were represented in the twenty articles. The simplest metric used to indicate food insecurity compared household food expenditure against a level of expenditure considered to be below the poverty line. Data on acquisition of food was commonly converted to available energy for the household using local food composition tables and expressed as a proportion of household total energy requirements. Dietary diversity was also assessed in some studies as well as experience of food insecurity. Conclusions: The review demonstrated that routinely collected HCES data sets provide a useful resource for the measurement of household food security in often resource-limited LMIC. Standardisation of methods used to assess food security is needed to allow for more useful comparisons between countries, as well as to assess temporal trends.